Reframing Debt in Buy Now Pay Later (BNPL) Schemes: A Phenomenological Study of Generation Z Consumers - Azzahra, Syifa; Saefullah, Aep; Vuthy, Ith (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
The rapid development of financial technology has acceleratedthe adoption of Buy Now Pay Later (BNPL) services as a keydigital financing alternative among Generation Z. While its easeof access, flexible payment schemes, and seamless digitalprocesses enhance convenience, BNPL also reshapes howconsumers perceive debt and manage personal finances. Thisstudy aims to explore the meaning of debt in BNPL usageamong Generation Z using a phenomenological approach,addressing the limited qualitative insights in prior researchdominated by quantitative methods. This study employs aqualitative phenomenological design, with data collectedthrough in-depth interviews with Generation Z BNPL users inIndonesia. The data were analysed using thematic analysis toidentify patterns of meaning derived from participants’ livedexperiences. The findings indicate that Generation Z tends tointerpret BNPL debt not as a conventional financial obligation,but as a practical and flexible payment method. Repeated usagefosters the normalization of debt within a digital lifestyle andcreates an illusion of financial control due to the emphasis onsmall instalment amounts. However, this perception alsointroduces potential financial risks and psychological pressureas obligations accumulate. This study concludes that BNPLdebt represents a socially constructed meaning shaped bysubjective experiences, social interactions, and the digitalconsumption context. The findings contribute to thedevelopment of behavioural accounting literature and providepractical implications for strengthening digital financial literacyand consumer protection policies targeting Generation Z.